Impact of Corporate Governance Attributes on Sustainability Reporting: Evidence from India - Khalada Sultana Choudhury; Jaynal Uddin Ahmed; Najul Laskar (Indonesian Journal of Sustainability Accounting and Management, 2022)
The study aimed to examine the impact of corporate governance attributes on sustainability reporting in the context of 435 non-financial companies from the top 500 BSE-listed companies based on market capitalization. The study is based on secondary data collected from the published sustainability, governance, and annual reports for a period of 6 years, that is, from 2015 to 2020. We have employed a content analysis technique to measure CSP using binary coding, that is, 0 (for non-disclosure) and 1 (for disclosure of item) based on the GRI reporting framework. Using panel data regression, we found that the corporate governance attribute plays an incredibly significant role in influencing the sustainability disclosure of Indian firms. Outcome of the regression results clearly indicates that except for independent directors all aspects of corporate governance, such as board size, gender diversity, and CEO duality have a positive and significant impact on Indian companies' corporate sustainability reporting practices indicating that they play a key role in influencing the reporting practices of Indian companies.